THE EFFECT OF TATO, COMPANY SIZE, AND LIQUIDITY ON PROFITABILITY OF AUTOMOTIVE COMPANIES LISTED ON IDX IN 2019-2024 PERIOD - Adriel Baringin Lombardi Montana Siahaan; Ni Putu Sri Harta Mimba (Adiba Aisha Amira, 2025)
The Indonesian automotive industry during 2019–2024 experienced significant dynamics due to COVID-19 and the government’s push for transformation toward electric vehicles. In this context, Profitability serves as a key indicator reflecting operational efficiency and corporate competitiveness. This study aims to analyze the effect of TATO measured using Total Asset Turnover ratio, firm size using natural logarithm of total assets, and liquidity using Current Ratio on probability measured by ROA. This research employs a quantitative associative causal approach with multiple linear regression analysis. The group studied includes 15 automotive companies chosen through purposive sampling, with a total of 64 data after elimination by outliers. The results shows that TATO provide a positive and significant impact on profitability, but firm size and liquidity do not provide significant impact. This study provides theoretical and practical implications for strategic decision-making by companies and for investor considerations in the automotive sector.